Notes on psychiatrist liability around the world regarding suicide - Saya, Anna; Albanesi, Giuseppe; Cichetti, Diego; Di Molfetta, Matteo; Guarino, Yuri; Niolu, Cinzia; Siracusano, Alberto (Frontiers in Psychiatry, 2025)
BackgroundCurrently, there is a lively debate regarding involuntary treatment and the psychiatrist's liability for suicide of patients with serious mental illness. This article aims to highlight the worldwide differences, considering that in some countries suicide is still considered a crime, while elsewhere, access to euthanasia/medically assisted suicide is allowed even for psychiatric patients.MethodsData have been collected from accredited sites, governmental websites, and databases of organizations. The legislation and socio-cultural contexts of different countries are considered.ResultsThis article highlight significant legislative differences, including suicide prevention programs, also due to several sociocultural patterns. The psychiatrist liability is not always clearly described in the legislation of different countries.ConclusionsWhat emerges from this study is the gray area of psychiatric patient suicide. Is it possible to make the psychiatrist liable for an unmanageable illness? What are the correct guidelines? When the possibility of coercion is no longer valid to avoid suicide and when does the right to self-determination begin for the psychiatric patient?